Раскопки городища Белинское и его некрополя в 2009 г. - Зубарев, В.Г. (Археологічні дослідження в Україні, 2010)
Excavations were conducted at two areas of Belinske hill-fort, the western and the southern. Fortification systems were studied and the layers from the last quarter of the 3rd c. to the first half of the 5th c. at the area of about 500 m2 were uncovered. At the necropolis four crypts of the 4th and the 5th centuries were discovered.